Motivations to interact with brands on Facebook – Towards a typology of consumer–brand interactions - Azar, Salim L. (2017)
In recent years, Facebook and other social media have become key players in branding activities. However, empirical research on consumer–brand interactions on Facebook is still in its infancy. Therefore, the aim of this research is to provide additional insights to brand managers on how to adapt their approaches to increase consumers’ interactions with brands on Facebook. In this study, we apply the uses and gratification theory proposed by Katz (1959) to develop a new typology of consumers based on consumer motivations to interact with brands on Facebook, and explore the type and intensity of these interactions. We identify five main motivations that might influence consumers’ interactions with a brand on Facebook: (1) social influence, (2) search for information, (3) entertainment, (4) trust and (5) reward. Building on these five motivations, a classification using clustering techniques reveals four different groups of consumers: (1) “brand detached”, (2) “brand profiteers”, (3) “brand companions” and (4) “brand reliants”. Our results provide valuable and applicable insights for social media marketing activities, which will assist brand managers to develop strategies for effectively reaching and influencing the most desirable groups of consumers.